Polymorphisms in Protein Tyrosine Phosphatase Non-receptor Type 2 and 22 (PTPN2/22) Are Linked to Hyper-Proliferative T-Cells and Susceptibility to Mycobacteria in Rheumatoid Arthritis - Sharp, Robert C.; Beg, Shazia A.; Naser, Saleh A. (Frontiers in Cellular and Infection Microbiology, 2018)
A shared genetic pre-disposition, chronic inflammation, and treatment with similar biologics between Rheumatoid arthritis (RA) and Crohn's disease (CD) have intrigued us to investigate whether the two disorders share trigger association or possible causation. We hypothesized earlier that Single Nucleotide Polymorphisms (SNPs) in the negative regulators Protein Tyrosine Phosphatase Non-receptor type 2 and 22 (PTPN2/22) lead to a dysregulated immune response, susceptibility to environmental triggers, and continued apoptosis as seen in chronic inflammation in RA and CD. To test the hypothesis, peripheral leukocytes samples from 132 consented subjects were genotyped for 9 SNPs in PTPN2/22 using TaqMan™ genotyping. The effect of the SNPs on PTPN2/22 and IFN-γ expression was determined using real time PCR. T-cell proliferation and response to phytohematoagglutonin (PHA) mitogen and mycobacterial antigens were determined by BrdU proliferation assay. Blood samples were also analyzed for the Mycobacterium avium subspecies paratuberculosis (MAP) IS900 gene by nPCR. Out of 9 SNPs examined, heterozygous (TC) or minor (CC) alleles of PTPN2:rs478582 occurred in 79% RA compared to 60% healthy controls (p-values ≤ 0.05; OR = 2.28). Similarly, heterozygous (GA) or minor (AA) alleles of PTPN22:rs2476601 occurred in 29% RA compared to 6% healthy controls (p-values ≤ 0.05; OR = 5.90). PTPN2/22 expression in RA was decreased by 1.2-fold compared to healthy controls. PTPN2:rs478582 upregulated IFN-γ in RA by 1.5-fold. Combined PTPN2:rs478582 and PTPN22:rs2476601 increased T-cell proliferation by 2.7-fold when treated with PHA. Surprisingly, MAP DNA was detected in 34% of RA samples compared to 8% healthy controls, (p-values ≤ 0.05, OR = 5.74). RA samples with PTPN2:rs478582 and/or PTPN22:rs2476601 were more positive for MAP than samples without polymorphisms. Combined occurrence of PTPN2:rs478582 and PTPN22:rs2476601 in association with the presence of MAP has significantly increased T-cell response and elevated IFN-γ expression in RA samples. The data suggest that genetic polymorphisms may play vital role in T-cell regulation, susceptibility to mycobacteria and ultimately response to treatment. This is the first study to report the detection of MAP DNA in the blood of RA patients; further studies are needed using larger number of samples.